Negotiating green space between ecological threats and beloved objects - Kerr, Thor (Taylor and Frances, 2015)
This paper is directed at furthering understandings of the function of space, time and sensory experience in environmental discourse. It does this through an empirical study of the publicity campaigns and counter-campaigns around North Port Quay, proposed as a sustainable property development project for coastal waters off Fremantle in Western Australia. The case demonstrates how a proposed ecological improvement project is contested in discursive struggles over the space and time of environmental problems. It shows how representations of an immediate threat to local environment can be more powerful than representations of a model solution to future global ecological crisis. The radical imposition of a futuristic island town by the beach triggered an effective, localized popular movement unified through people’s desire to restore their sensual experiences of local environment. This desire linked people’s diverse demands for conservation behind a discursive frontier against anyone supporting North Port Quay. Standing for ‘our beaches’ against the proposed sustainable development not only blocked the project through localized practices of institutional democracy, it also helped transform the institutional political landscape of Fremantle.